Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.7 Hyperbolic Functions - 6.7 Exercises - Page 490: 35



Work Step by Step

Given: $G(t)=\dfrac{d}{dt}\sinh {(\ln t)}$ Now, $G'(t)=\dfrac{d}{dt}\sinh {(\ln t)}$ On applying the chain rule, we have $G'(t)=(\dfrac{d\sinh {(\ln t)}}{d\ln t})(\frac{d\ln t}{dt})$ or, $=\cosh {(\ln t)} \times \dfrac{1}{t}$ or, $=\dfrac{\cosh {(\ln t)}}{t}$ Since, $\cosh x=\dfrac{e^x+e^{-x}}{2}$ $G'(t)=\dfrac{\dfrac{e^{\ln t}+e^{-\ln t}}{2}}{t}=\dfrac{t+\frac{1}{t}}{2t}$ or, $=\dfrac{\frac{t^2+1}{t}}{2t}$ or, $=\dfrac{t^2+1}{2t^2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.